Performance Evaluation of Collard Based Bio-Filter for Treating Fish Tank Effluent for Re-use - Grism Lawrence, Obeti; Wanyama, Joshua; Banadda, Noble; Candia, Alphonse; George Onep, Samuel; Walozi, Ronald (Journal of Environmental Science and Engineering, 2019)
The increasing Uganda’s urban population growth has led to limited space coupled with high cost of living, thus making it difficult for the urban poor in congested areas to afford fish protein hence poor nutrition among the low income earners. Therefore this study was conducted to evaluate the performance of collard based bio-filtration system for filtering fish tank effluent for re-use in congested peri-urban areas. Field physical-chemical parameters (ammonia, nitrate, dissolved oxygen, temperature and pH) were measured at various bio-filter lengths in the effluent from both collard based and GBF (Gravel Based Bio-Filter). Differences in mean ammonia and nitrate levels at various lengths were analyzed using one-way ANOVA at p = 0.05. Ammonia levels were significantly reduced (p < 0.05) at various lengths: L0 99.1 mg/L; L1 75.8 mg/L (23.6%); L2 53.1 mg/L (46.4%); L3 25.8 mg/L (74%) and L4 6.6 mg/L (93.4%). Similarly, nitrate levels significantly reduced (p < 0.05): L0 11.8 mg/L; L1 7.2 mg/L (39.4%); L2 3.6 mg/L (69.2%); L3 1.6 mg/L (86.7%) and L4 0.1 mg/L (99.3%). Significant difference (p < 0.05) was obtained in mean ammonia and nitrate removal between collard based and gravel bio-filters. Collard based filter yielded higher ammonia and nitrate removal at L4 by 18.3% and 39.5% respectively, hence L4 is the effective length for collard based bio-filter.
Keywords: Effluent; Bio-filter; Nitrifying bacteria; Ammonia